2019
DOI: 10.1038/s41419-019-1641-y
|View full text |Cite
|
Sign up to set email alerts
|

Delineating the role of eIF2α in retinal degeneration

Abstract: Activation of the unfolded protein response has been detected in various animal models of retinal degeneration. The PERK branch converges on eIF2α to regulate protein synthesis. We previously reported that diseased retinas produce less protein as they degenerate. We also proposed that the majority of this reduction in protein synthesis may not be due to control of eIF2α. Nevertheless, multiple research groups have reported that modulating eIF2α levels may be a viable strategy in the treatment of neurodegenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
2
7
1
Order By: Relevance
“…Although some literature suggests that PERK pathway stimulation via interventions like Salubrinal can be neuroprotective via prolonged increases in p-eIF2α (Starr and Gorbatyuk, 2019;Athanasiou et al, 2017) or nrf2 (Comitato et al, 2020), we do not show similar protection in this model. Nor do we show protection when decreasing activation of this pathway, as others have reported with both ISRIB (Chou et al, 2017;Wenzhu Zhou et al, 2023) and other interventions against downstream proteins like ATF4 or CHOP in models of TBI (Hu et al, 2019;Neill and Masson, 2023;Pitale et al, 2017;Song et al, 2008).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although some literature suggests that PERK pathway stimulation via interventions like Salubrinal can be neuroprotective via prolonged increases in p-eIF2α (Starr and Gorbatyuk, 2019;Athanasiou et al, 2017) or nrf2 (Comitato et al, 2020), we do not show similar protection in this model. Nor do we show protection when decreasing activation of this pathway, as others have reported with both ISRIB (Chou et al, 2017;Wenzhu Zhou et al, 2023) and other interventions against downstream proteins like ATF4 or CHOP in models of TBI (Hu et al, 2019;Neill and Masson, 2023;Pitale et al, 2017;Song et al, 2008).…”
Section: Discussioncontrasting
confidence: 99%
“…For example, it was found that targeting p-eIF2α, both by systemic GADD34 knockout and photoreceptor specific PERK knock out, in a model of inherited retinal degenerative disease was not protective. Instead, retinal cells might be required to activate alternative pathways for protein synthesis control (Starr and Gorbatyuk, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…ER stress is a defensive response to a host of stimulants, but it can evolve to encompass cell injury [35]. PERK/eIF2α is one of the main pathways for ER stress-mediated apoptosis [36]. However, recent studies have shown that increasing eIF2α phosphorylation protected injured cells [37].…”
Section: Discussionmentioning
confidence: 99%
“…These mice expressed truncated CEP290, manifested chronic ISR activation, and developed severe RD rapidly, thus modeling Leber congenital amaurosis 10 and RP in humans. We demonstrated that GADD34-mediated manipulation with the p-eIF2α level in rd16 photoreceptors does not modify the translation rate and has no major impact on retinal function in mice with ciliopathies, although GADD34 ablation slowed down the rate of apoptotic cell death [2]. This is why we have become interested in understanding whether the GADD34-mediated elevation of p-eIF2α in retinas degenerating at a slower pace alters the progression of retinal dystrophy in mice.…”
Section: Introductionmentioning
confidence: 98%